KEWAJIBAN MENYIMPAN PROTOKOL NOTARIS DAN AKIBAT HUKUMNYA MENURUT HUKUM POSITIF INDONESIA - Benny Krestian Heriawanto (Arena Hukum, 2018)
AbstractThis article is designed to investigate and analyze the legal consequence of non-performance obligation to keep the Notary protocol by a Notary. Performing the position, a notary is required to behave in a certain way, some of the behaviors are recognized as ethical behavior which is stipulated in the ethic code and as obligation that is established by Notary Profession Act. One of the behaviors demand is the obligation to keep the Notary protocol and cause legal consequence for the non-fulfillment obligation.. This article is analyzed with Normative Legal Research Method with statute and conceptual approach. Based on the study and analysis can be concluded that the violation of the obligation, Notary who is proven intentionally or negligently perform the obligation of Notary to save Notary protocol, there are responsibility and/or accountability that cause legal consequence, in the form of sanctions both administrative, civil and even criminal. AbstrakArtikel ini disusun bertujuan untuk mengkaji dan menganalisis akibat hukum atas tidak dilaksanakannya kewajiban menyimpan Protokol Notaris oleh seorang Notaris. Dalam melaksanakan tugas jabatan, Notaris dituntut untuk berperilaku dengan cara tertentu, sebagian perilaku tersebut diakui sebagai perilaku etis yang diatur dalam kode etik dengan kewajiban yang ditetapkan oleh Undang undang tentang Jabatan Notaris. Salah satu tuntutan perilaku tersebut adalah kewajiban menyimpan protokol Notaris dan tidak dipenuhinya kewajiban tersebut menimbulkan akibat hukum. Artikel ini disusun dengan normatif legal research metode dengan pendekatan peraturan perundang-undangan dan konseptual. Berdasarkan hasil kajian dan analisa dapat disimpulkan bahwa dengan dilanggarnya kewajiban tersebut, Â Notaris yang terbukti dengan sengaja atau lalai melaksanakan kewajiban untuk menyimpan protokol Notaris terdapat tanggung jawab dan/atau tanggung gugat yang melahirkan akibat hukum berupa sanksi baik administratif, perdata dan bahkan pidana.